1999
DOI: 10.1889/1.1985279
|View full text |Cite
|
Sign up to set email alerts
|

TFT‐addressed full‐color reflective‐type display using mixed‐mode twisted‐nematic LCD

Abstract: Abstract— A high‐performance reflective‐type TFT‐LCD with full‐color and video‐rate capabilities has been developed. This display utilizes a single‐polarizer geometry associated with a mixed‐mode twisted‐nematic (MTN) effect. The twist angle of the liquid‐crystal cell is optimized by evaluating the light efficiency, contrast ratio, chromaticity, and gray‐shading reproducibility with respect to the variation of cell‐gap uniformity. Attractive features of this display such as low driving voltage, fast response, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Figure 3. When this plot is compared with previous published data [4], it is found that LCDs which have twists of 70°, 80°, and 90° and ∆nd values of 0.275, 0.26, and 0.24 µm, respectively, have decreasing brightness which is seen above, marked by dots. LCD is not nearly as good as that of the 70°, 80°, or 90°, therefore the 100° twist cell is not normally used for displays.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Figure 3. When this plot is compared with previous published data [4], it is found that LCDs which have twists of 70°, 80°, and 90° and ∆nd values of 0.275, 0.26, and 0.24 µm, respectively, have decreasing brightness which is seen above, marked by dots. LCD is not nearly as good as that of the 70°, 80°, or 90°, therefore the 100° twist cell is not normally used for displays.…”
Section: Resultssupporting
confidence: 50%
“…Enlarged region of interest for the reflectance contour plot fromFigure 5. When this plot is compared with previous published data[4], it is found that LC cells which have twists of 70°, 80°, and 90° and ∆nd values of 0.275, 0.26, and 0.24 µm, respectively, have decreasing darkness which is seen above, marked by dots.…”
supporting
confidence: 51%
See 1 more Smart Citation